Induced resistance for plant defence : (Blackwell Pub., 2007)
Plant diseases worldwide are responsible for billions of dollars worth of crop losses every year. With less agrochemicals being used and less new fungicides coming on the market due to environmental concerns, more effort is now being put into the use of genetic potential of plants for pathogen resistance and the development of induced or acquired resistance as an environmentally safe means of disease control.